2021
DOI: 10.15678/ier.2021.0703.06
|View full text |Cite
|
Sign up to set email alerts
|

Do entrepreneurial characteristics and education influence start-up potentials among undergraduates? Evidence from a developing country

Abstract: Entrepreneurship education offers plausible policy options to curtail the consistent rise in youth unemployment in Nigeria. Understanding students' entrepreneurial characteristics will assist university administrators, policymakers, scholars and practitioners to deliver contents that stimulate their entrepreneurial propensity. This study examines students' entrepreneurial characteristics and how it, together with entrepreneurship education, shapes start-up potential among them in Nigeria. Research Design & Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The results in Olofinyehun et al (2022) also suggest that family support influences the intention to become an entrepreneur among students. In Ezeh et al (2020) and Adelowo et al (2021aAdelowo et al ( , 2021b educational support and perceived behavioural control were found to be significant predators of entrepreneurship among students within the two different contexts.…”
Section: Relationship Among Entrepreneurial Intention Social Support ...mentioning
confidence: 85%
See 4 more Smart Citations
“…The results in Olofinyehun et al (2022) also suggest that family support influences the intention to become an entrepreneur among students. In Ezeh et al (2020) and Adelowo et al (2021aAdelowo et al ( , 2021b educational support and perceived behavioural control were found to be significant predators of entrepreneurship among students within the two different contexts.…”
Section: Relationship Among Entrepreneurial Intention Social Support ...mentioning
confidence: 85%
“…In fact, entrepreneurship has been argued to promote rapid economic growth as well as reduce the rate of unemployment (Ogunlana, 2018;Siyanbola, 2019;Adelowo et al, 2021b;Ezeh et al, 2020). Unemployment is a major problem in Nigeria (Adelowo et al, 2021b). To paint the picture of unemployment in the country more starkly, Figure 1 shows a consistent increase in the rate of unemployment even before the COVID-19 pandemic hit.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations